2004
DOI: 10.5194/angeo-22-3899-2004
|View full text |Cite
|
Sign up to set email alerts
|

Convective activities associated with intraseasonal variation over Sumatera, Indonesia, observed with the equatorial atmosphere radar

Abstract: Abstract. The influence of intraseasonal variation (ISV) on convective activities over Sumatera (or Sumatra) is studied by using data derived from the Equatorial Atmosphere Radar (EAR), the Boundary Layer Radar (BLR), the surface weather station, the Geostationary Meteorological Satellite (GMS), and NCEP/NCAR reanalysis. In June 2002, convective activities over the Indian Ocean, the maritime continent, and the western Pacific were significantly modulated by the ISV. Zonal wind observed by EAR and surface press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…There have been numerous studies on the rainfall variability over Indonesia and its relation to the diurnal change (Mori et al, 2004;Seto et al, 2004;Ichikawa and Yasunari, 2006;Tian et al, 2006;Qian, 2008), the annual change like monsoon (Hamada et al, 2002;Aldrian and Susanto, 2003;Chang et al, 2005) and the interannual large-scale climatic phenomena such as the El Niño-Southern oscillation (Kirono et al, 1999;Haylock and McBride, 2001;McBride et al, 2003;Aldrian and Susanto, 2003;Hendon, 2003;Chang et al, 2004). It is also widely known that the Madden-Julian Oscillation (MJO; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on the rainfall variability over Indonesia and its relation to the diurnal change (Mori et al, 2004;Seto et al, 2004;Ichikawa and Yasunari, 2006;Tian et al, 2006;Qian, 2008), the annual change like monsoon (Hamada et al, 2002;Aldrian and Susanto, 2003;Chang et al, 2005) and the interannual large-scale climatic phenomena such as the El Niño-Southern oscillation (Kirono et al, 1999;Haylock and McBride, 2001;McBride et al, 2003;Aldrian and Susanto, 2003;Hendon, 2003;Chang et al, 2004). It is also widely known that the Madden-Julian Oscillation (MJO; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller correlation coefficient in meridional wind suggests that contributions of local-scale phenomena were greater for meridional wind. Previous studies showed that radar zonal wind shows consistent change with synoptic-scale disturbances such as ISV (Seto et al 2004;Shibagaki et al Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Murata et al (2006) have shown that an intensification of westerly wind accompanied by SCC can cause a dry-air intrusion from the Indian Ocean to Sumatra in the lower and middle troposphere, and suggested that an appearance of dry air plays a role in suppressing convective activity over Sumatra. Seto et al (2004) also reported that the Sumatra region became convectively inactive after an intensification of lower-tropospheric westerly wind.…”
Section: Introductionmentioning
confidence: 99%
“…Murata et al (2002) suggested that quasi-10-day variations of convective activity over Sumatra changed in association with synoptic-scale variations of lower-tropospheric zonal wind over the Indian Ocean and Sumatra. Seto et al (2004) have shown a relationship between intraseasonal variability (ISV, see Zhang (2005) and Madden and Julian (1994)) and convection over the mountainous region of Sumatra by a case study during June 2002. They showed that convection caused by topographically-induced local circulation was prominent over the mountainous region of Sumatra during the inactive phase of ISV.…”
Section: Introductionmentioning
confidence: 99%